Performance evaluation of an efficient five input majority gate design in QCA nanotechnology - Amanpreet Sandhu; Sheifali Gupta (International Journal of Reconfigurable and Embedded Systems (IJRES), 2019)
Quantum-dot-cellular-automata (QCA) is the imminent transistor less technology, considered at nano level with high speed of operation and lower power dissipation features. The present paper proposes a novel and an efficient 5-input coplanar majority gate (PMG) with improved structural and energy efficiency. The proposed gate consumes an occupational area of 0.01μm2 with 17 QCA cells which is 50% less in comparison to the best designs reported in literature. The proposed structure is also more energy efficient because it dissipates 21.1% less energy than the best reported designs. The correctness of a proposed majority gate is verified by designing a single bit full adder. The new 1-bit full adder design is structural efficient and robust in terms of gate count and clock delay. It consumes occupational area of 0.05μm2 with 58 QCA cells showing 16.6% improvement in structural efficiency as compared to the best design reported in. It is having a gate count of 4 with the delay of 1 clock cycle. Here, the QCADesigner and QCAPro tools are utilized for the simulation and energy dissipation analysis of proposed majority gate and full adder design.